Factors associated with obesity and metabolic syndrome in ageing black South African women - Gradidge, Philippe Jean-Luc (Glob Health Action, 2017)
Background: The incidence of obesity and related metabolic diseases is high and increasing in sub-Saharan African women. Evidence on the determinants of these diseases is limited, particularly in black South African women. Objective: This PhD review attempts to understand the determinants of obesity and metabolic syndrome (MetS) in a population of ageing urban-dwelling black South African women. Methods: Drawing on the longitudinal Birth-to-Twenty-Plus cohort, data were collected in 2002/03 and 2012/13, including information on behavioural factors (smoking, sitting time, physical activity, smokeless tobacco, and alcohol consumption), body-size perception, body composition (measures of adiposity and lean mass), blood pressure, and cardiometabolic biomarkers (lipid profile, fasting insulin, fasting blood glucose, insulin resistance, leptin, and adiponectin). Results: The prevalence of obesity and related cardiovascular disease risk was high and increased significantly over the 10 year period. Despite most of the study population being physically active, sitting time was high and associated with elevated blood pressure and hypertriglyceridaemia. Two groups of people were observed, those who were happy and those who were unhappy with their body size. In logistic regression analysis, the risk of MetS was lowered by abdominal subcutaneous adipose tissue and adiponectin, and increased by age, smoking, truncal lean mass, and insulin resistance. Conclusions: Obesity was confirmed to be increasing in black South African women, despite most women being sufficiently active according to guidelines of ≥150 min activity/week. Nevertheless, the contribution of sitting time to poor health outcomes is evident in this study population and must be addressed, particularly in women who are content with being obese. The novel finding of the effects of abdominal subcutaneous tissue and truncal lean mass with MetS requires further investigation. The protective effect of adiponectin against MetS is an important finding which highlights the novel interaction between adiposity and cardiometabolic diseases in black South African women.